C1QTNF6 is a Prognostic Biomarker and Related to Immune Infiltration and Drug Sensitivity: A Pan-Cancer Analysis - Liu, Wei; Zhang, Jian; Xie, Tao; Huang, Xiaoting; Wang, Baiyao; Tian, Yunhong; Yuan, Yawei (Frontiers in Pharmacology, 2022)
Background: The discovery of reliable cancer biomarkers could tune a diagnosis and improve the way patients are treated. However, many cancers lack robust biomarkers. C1QTNF6 has been preliminarily elucidated for its role in some tumors. However, no pan-cancer analysis has been performed to comprehensively explore the value of C1QTNF6. Methods: Data from the TCGA database, GTEx database stored in the USUC Xena were used for analyzing the profiles of C1QTNF6 expression in normal and tumor tissues in pan-cancer. Subsequently, the gene alteration rates of C1QTNF6 were acquired on the online web cBioportal. With the aid of the TCGA data, the association between C1QTNF6 mRNA expression and copy number alterations (CNA) and methylation was determined. Survival analyses of C1QTNF6 were carried out. Moreover, the tumor biological and immunological characteristics of C1QTNF6 were clarified in the forms of the correlation between C1QTNF6 expression and hallmark Pathway scores in MsigDB database, immune cell infiltration, immune-related genes. We conducted a GSEA of C1QTNF6 to illustrate its potential biological functions. In addition, GDSC2 data with 198 drugs were adopted to explore drug sensitivity with the change of C1QTNF6 expression. . Result: C1QTNF6 was overexpressed in many types of cancer, Survival analysis showed that C1QTNF6 independently served as a prognostic indicator for poor survival in many tumors. Besides, we also identified a positive correlation between C1QTNF6 and cancer hallmark pathway score, tumor microenvironment related pathways score (TME score), and immune characteristic. In terms of drug sensitivity analysis, we found higher expression level of C1QTNF6 predicts a high IC50 value for most of 198 drugs which means drug resistance. Conclusions: Our study provides a new biological marker for cancer, which is beneficial to the diagnosis and treatment of cancer.